Utilization of Organic Fertilizer on Sweet Corn (Zea mays saccharata Sturt) Crop at Shallow Swamp Land - Midranisiah; Marlina Neni; Rahim S.E; Hawayanti Erni (MATEC Web of Conferences, 2017)
Shallow lowland swamp area has significant potential for cultivation of sweet corn crop. This lowland swamp has rich natural resources such as organic fertilizers from chicken dunk, cow dunk, oil palm fresh bunches and legume cover crops (LCC) that are not maximally utilized yet by farmers. These organic fertilizers can be utilized to increase the growth and production of sweet corn crop. The research objective was to determine organic fertilizer types that capable to increase the growth and production of sweet corn crop at shallow lowland swamp area. This research had been conducted from January to April 2015 in Pulau Semambu Village, North Indralaya Subdistrict, Ogan Ilir District, South Sumatra Province. The design used in this research was non-factorial Randomized Block Design (RBD) with four treatments of organic fertilizer types with six replications for each treatment. The treatments were consisted of organic fertilizers from chicken dunk, cow dunk, oil palm fresh bunches and legume cover crops (LCC). The results showed that treatment of organic fertilizers from chicken dunk could increase the growth and production of sweet corn at shallow lowland swamp area with yield level of 4.37 kg.plot −1.